Pulse electroplating of copper film : a study of process and microstructure - Zhang, X. (2012)
Copper films with high density of twin boundaries are known for high mechanical strength with little tradeoff in electrical conductivity. To achieve such a high density, twin lamellae and spacing will be on the nanoscale. In the current study, 10 microm copper films were prepared by pulse electrodeposition with different applied pulse peak current densities and pulse on-times. It was found that the deposits microstructure was dependent on the parameters of pulse plating. Higher energy pulses caused stronger self-annealing effect on grain recrystallization and growth, thus leading to enhanced fiber textures, while lower energy pulses gave rise to more random microstructure in the deposits and rougher surface topography. However in the extremes of pulse currents we applied, the twin densities were not as high as those resulted from the medium or relatively high pulse currents. The highest amount of nanoscale twinning was found to form from a proper degree of self-annealing induced grain structure evolution. The driving force behind the self-annealing is discussed.